iPads in Breast Imaging - A Phantom Study - Hammon, Matthias; Schlechtweg, Philipp; Schulz-Wendtland, Rüdiger; Uder, Michael; Schwab, Sibylle (Geburtshilfe und Frauenheilkunde, 2014)
Introduction: Modern tablet PCs as the iPad are becoming more and more integrated into medicine. The aim of this study was to evaluate the display quality of iPads regarding digital mammography. Materials and Methods: Three experienced readers compared the display quality of the iPad 2 and 3 with a dedicated 10 megapixel (MP) mammography liquid crystal display (LCD) screen in consensus using the standardized Contrast Detail Mammography (CDMAM) phantom. Phantom fields without agreement between the readers were classified as "uncertain", correct 2 : 1 decisions were classified as "uncertain/readable". In a second step display quality of the three reading devices was judged subjectively in a side by side comparison. Results: The 10 MP screen was superior to both iPads in 4 (phantom-)fields and inferior in 2 fields. Comparing the iPads, version 3 was superior in 4 fields and version 2 was superior in 1 field. However these differences were not significant. Total number of "uncertain" fields did not show significant differences. The number of "uncertain" fields was 15 with the 10 MP screen, 16 with the iPad 2 and 17 with the iPad 3 (p > 0.05), the number of "uncertain/readable" fields was 4, 7 and 8, respectively. Subjective image quality of the iPad 3 and the 10 MP screen was rated superior to the iPad 2. Conclusion: The evaluated iPads, especially in version 3, seem to be adequate to display mammograms in a diagnostic quality and thus could be useful e.g. for patient consultation, clinical demonstration or educational and teaching purposes. However primary mammogram reading should still be performed on dedicated large sized reading screens.
EVALuna2:14368